2008
DOI: 10.1007/s11910-008-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in brain tumor patients

Abstract: As effective treatment interventions have increased survival rates, there has been greater awareness that many brain tumor patients experience cognitive dysfunction despite adequate disease control. Cognitive difficulties often have an impact on quality of life and interfere with the patient's ability to function at premorbid levels. A review of the literature indicates that whole-brain radiotherapy alone or in combination with chemotherapy results in more pronounced cognitive dysfunction than either partial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
1
1
4
Order By: Relevance
“…Quanto a faixa etária mais frequente foi entre 31 e 77 anos e o ambos gêneros são mencionados. Bosma et al, 2008;Campennı et al, 2015;Curey et al, 2012;Otten et al, 2012;Prabhu et al, 2010 os autores relataram déficits neuropsicológicos sem utilizar avaliações neuropsicológicas formais, somente por meio de exames de imagem (Amiez et al, 2008;Bauer et al, 2007;Baxendale et al, 2013;Bizzi et al, 2012;Blonski et al, 2012;Bosma et al, 2008;Braun et al, 2008;Campanella et al, 2008;Campennı et al, 2015;Cipolotti et al,2015;Correa, 2008;Curey et al, 2012;Fleming et al, 2014;Fliessbach et al, 2010;Gehring et al, 2009;Gennaro et al, 2006;Giovagnoli et al, 2007;Goebel et al, 2013;Huang et al, 2014;Maesawa et al, 2015;Meguins et al, 2015;Miotto et al, 2011;McDuff et al, 2013;Mu et al, 2012;Noll et al, 2014;Nomura et al, 2013;Otten et al, 2012;Prabhu et al, 2010;Ralph et al, 2010;Satoer et al, 2014;Talacchi et al, 2013) . Estas informações podem ser observadas na Tabela 1.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Quanto a faixa etária mais frequente foi entre 31 e 77 anos e o ambos gêneros são mencionados. Bosma et al, 2008;Campennı et al, 2015;Curey et al, 2012;Otten et al, 2012;Prabhu et al, 2010 os autores relataram déficits neuropsicológicos sem utilizar avaliações neuropsicológicas formais, somente por meio de exames de imagem (Amiez et al, 2008;Bauer et al, 2007;Baxendale et al, 2013;Bizzi et al, 2012;Blonski et al, 2012;Bosma et al, 2008;Braun et al, 2008;Campanella et al, 2008;Campennı et al, 2015;Cipolotti et al,2015;Correa, 2008;Curey et al, 2012;Fleming et al, 2014;Fliessbach et al, 2010;Gehring et al, 2009;Gennaro et al, 2006;Giovagnoli et al, 2007;Goebel et al, 2013;Huang et al, 2014;Maesawa et al, 2015;Meguins et al, 2015;Miotto et al, 2011;McDuff et al, 2013;Mu et al, 2012;Noll et al, 2014;Nomura et al, 2013;Otten et al, 2012;Prabhu et al, 2010;Ralph et al, 2010;Satoer et al, 2014;Talacchi et al, 2013) . Estas informações podem ser observadas na Tabela 1.…”
Section: Resultsunclassified
“…Em relação aos prejuízos de memória, os estudos variaram em termos das informações prestadas e do tipo de prejuízo encontrado. Dos 19 estudos que mencionaram prejuízos de memória, 10 estudos não especificaram se estas dificuldades seriam de natureza verbal, visuoespacial, episódica ou operacional (Amiez et al, 2008;Bosma et al, 2008;Correa, 2008;Fliessbach et al, 2010;Gehring et al, 2009;McDuff et al, 2013;Meguins et al, 2005;Noll et al, 2014;Prabhu et al, 2009;Satoer et al, 2014). Sabe-se, no entanto, que os sistemas de memória não são um construto unitário.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Therefore, although a comprehensive assessment would be ideal, it is important to employ brief test batteries in order to accommodate this constraint and to minimize effects due to patient fatigue. 14 The present study was designed to examine the feasibility of enrolling and measuring cognitive function, using ageappropriate measures, in a sample of pediatric brain tumor patients prior to their undergoing surgery. First, to address feasibility we report on rates of accrual into the study, completion of performancebased neurocognitive function, and parent-reported assessment of patients' neurocognitive function prior to surgery.…”
Section: Neuro-oncology Practicementioning
confidence: 99%